Chemistry : - Silberberg, Martin Stuart (McGraw-Hill, 2009)
Contains macroscopic to microscopic molecular illustrations, consistent step-by-step worked exercises in every chapter, and an extensive range of end-of-chapter problems which provide engaging applications covering a wide variety of freshman interests, including engineering, medicine, materials, and environmental studies.